Analysis Of The Ease And Usability Of The My-Dd Zis Online Application Dompet Dhuafa With TAM And IPA Approach - Titi Haryani; Laila Septiana (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2022)
Dompet Dhuafa is a charitable institution dedicated to empowering people and humanity through the management of Zakat, Infaq, Alms, Waqf Funds (ziswaf) and other social funds that are managed in a modern and reliable manner. In its implementation, it certainly introduces the concept of compassion as the root of the charity movement that carries out five program pillars: health, education, economics, social, and dowry and culture. In an effort to improve services, Dompet Duafa launched the My-DD ZIS application to make it easier for the public to be able to pay zakat, infaq, alms and online donations easily and quickly. However, so far no research has been conducted on the extent of acceptance of the ease of use of the My-DD ZIS Online Dompet Dhuafa application, therefore this study was conducted to determine the extent to which the ease of use of applications through the TAM and IPA approaches was conducted. In this study, the population was taken based on users of the My-DD ZIS Online Dompet Dhuafa application for four months, namely from January to April 2022 and from the results of the gap analysis it was found that in general users of the My-DD ZIS Online Dompet Dhuafa application were not satisfied with the application. the current My-DD ZIS Online Dompet Dhuafa application.